Effect of Alkaline Treatment on Physical and Tensile Properties of Areca Leaf Sheaths (ALSs) used for Biodegradable ALS Plate Production - Pasuta Sungsee; Narita Khundamri; Wittaya Wongklang; Anurak Tripetch; Paemika Saetiaw; Suwat Rattanapan (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
This research evaluated the possibility of alkaline treatment to solve the problem of molding due to moisture during storage of areca leaf sheaths (ALSs) to be used for biodegradable ALS plate production. The effect of alkaline treatment on the properties of ALSs was studied. Sodium hydroxide (NaOH) and sodium bicarbonate (NaHCO3) were used as chemicals for surface treatment. The solution of NaOH and NaHCO3 was varied at 1%, 3%, and 5% w/v. Surface treatment with NaOH and NaHCO3 partially removed hemicellulose, cellulose, lignin, and impurities from the surface of the ALSs and increased the moisture resistance property of the ALSs. Treatment with NaOH made the ALSs’ surface rougher, whereas treatment with NaHCO3 had no effect on the surface of the ALSs. The decomposition temperature (Td2) of the NaOH-treated ALSs decreased by approximately 7.0 to 10.5%, while for the NaHCO3-treated ALSs it changed only slightly. The overall tensile properties of the NaOH-treated ALSs were better than those of the NaHCO3-treated ALSs. The surface treatment with 1% NaOH and 1% NaHCO3 increased the tensile modulus by 20.5% and 6.2%, respectively, as compared with the nontreated ALS. It was found that surface treatment with 1% NaOH and 1% NaHCO3 could create suitable conditions for ALS plate production. This work is a preliminary study; more research still needs to be done.